Wyposażenie wnętrz klasztornych i kościelnych w Krakowie jako źródło do wiedzy o kulturze mieszczańskiej XV—XIX wieku (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
INTERIOR FURNISHINGS OF CRACOW CLOISTERS AND CHURCHES AS A SOURCE OF INFORMATION ABOUT BURGHERS’ CULTURE (15TH-19TH CENTURIES)The monuments of the artistic and material culture of Cracow burghers are very scarce today. Old inventory lists and burghers’ testaments along with guild mementos, mainly chests, counters and special chalices (wilkomas) in the collection of the Historical Museum of the City of Cracow can give some idea about those monuments. Some items registered during the forty year — work on the Catalogue of Historical Monuments of the City of Cracow may help to bring back the old burghers culture. Four parts of the catalogue (eleven volumes) have been published since 1965.Apart from architectural details (doors, panellings, wall cabinets), especially interesting are cabinet-making products in cloisters and churches. These include benches, chairs, tables, cupboards and chests from the 15th through 19th centuries, which survieved until the present day. They were manufactured locally in Cracow or were imported from other places (e.g. from Gdansk).Jewellery and goldsmithery form another important group. Jugs, kettles, and bowls dating back to as far as the 15th century, can be listed among items that may have also served secular purposes. Jewellery is important for the research on the burgher culture. We can find works of jewellery on reliquiaries, monstrances and silver robes made for the holy icons in the Baroque times. In cloister and church treasuries and sacristies there are many canonicals dating back as far as the 15th century. These are not only chasubles, copes and dalmatics, but tabernacle curtains, tapestries hung on church walls on special occasions, and other kinds of weaving works as well. At least part of them, mostly from Italy and France, may have been donated by burghers and were originally adorning Cracow burghers’ houses; that refers also to locally manufactured embroidery.Very important collections of historical mementos preserved in Cracow churches and cloisters belong to the heritage of material culture. These are various articles in wood, copper and other metals, glass and marble. Old kitchen utensils have been preserved, including vessels and moulds; tools used in spinning and embroidering; sand-glasses; and pharmacy eguipment including mortars and vessels.Unfortunately, many of such items, especially from the 19th century, have been destroyed due to lack of understanding.It is sometimes difficult to say whether paintings and prints kept in churches and cloisters come from burghers’ houses or not. Small paintings on religious subjects may have come from burghers’ houses. Genre paintings, landscapes or paintings on historic subjects (the Dominican cloister and the cloister of the Visitant Sisters) are even more likely of the same provenance.The similar things can be said about prints preserved in Cracow cloisters. There are many of them, mostly on religious subjects. Complete cycles representing scenes from the life of saints have been preserved. The oldest prints date from the 16th century.Large in size copperplates decorate cloisters even today, hanging on the walls in corridors.As it is known that burghers’ houses were decorated with prints, the prints from cloister collections can be used as material for comparative studies on Cracow burghers’ houses.The issues presented in the article may serve as an introduction to a monographic research which should be done on burghers’ house furnishings and which should cover various fields of art and material culture. However, even today it can be stated that Cracow cloister collections are an excellent source for research on Cracow’s cultural heritage.